Penyuluhan Budaya Baca bagi Guru di TK Kristen Haleluyah Jakarta Pusat (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2023)
The development of the times demands that everything can quickly accept change. This change occurs in almost all aspects of life, including the development of education in kindergarten. Indonesian is an important part of education. The importance of learning Indonesian because in it there are four aspects of language skills. Each skill has its own role and function. Likewise with reading skills in children. These skills are considered important in kindergarten education because children have started to be prepared for a higher level of education, namely elementary school. The habit or form of cultivating reading is very important because there will be many benefits for children. Culture has a simple meaning, namely something that is used to. Therefore, the culture of reading in the Kindergarten education environment is something that must be paid close attention to because children will be accustomed to and trained to read from an early age.